2001
DOI: 10.1089/105072501300176363
|View full text |Cite
|
Sign up to set email alerts
|

Update on Intrathyroidal Iodine Metabolism

Abstract: The thyroid concentrates iodide from the serum and oxidizes it at the apical membrane, attaching it to tyrosyl residues within thyroglobulin (Tg) to make diiodotyrosine and monoiodotyrosine. Major players in this process are Tg, thyroperoxidase (TPO), hydrogen peroxide, pendrin, and nicotinamide adenine dinucleotide phosphate (NADPH). Further action of TPO, hydrogen peroxide (H2O2), and iodinated Tg produce thyroxine (T4) and triiodothyronine (T3). Hormone-containing Tg is stored in the follicular lumen, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 70 publications
2
109
0
6
Order By: Relevance
“…The TPO enzyme, which is highly conserved among vertebrates, catalyzes the iodination of tyrosyl-residues in TG and their subsequent coupling to iodothyronines (Dunn and Dunn, 2001). The findings of our study showed that after exposure to DE-17, the transcription of TPO gene showed a trend toward but not a significant increase in the transcription of the TPO gene.…”
Section: Discussionmentioning
confidence: 51%
“…The TPO enzyme, which is highly conserved among vertebrates, catalyzes the iodination of tyrosyl-residues in TG and their subsequent coupling to iodothyronines (Dunn and Dunn, 2001). The findings of our study showed that after exposure to DE-17, the transcription of TPO gene showed a trend toward but not a significant increase in the transcription of the TPO gene.…”
Section: Discussionmentioning
confidence: 51%
“…TPO catalyzes the iodination of tyrosyl residues in TG and their coupling into iodothyronines (Dunn and Dunn, 2001). In the present study, TPO gene expression remained unchanged while a down-regulation of TG gene expression was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of RNA translation factors indicates that one arm of the TSH-induced cellular response in the amphibian thyroid aims at augmenting global translation rates. The upregulation of various genes implicated in ER function and vesicular protein transport is likely related to another major hallmark of TSH action, namely the stimulation of synthesis and secretion of TG, the main secretory product of thyroid follicular cells (Dunn and Dunn, 2001). The expression signature detected for transcripts related to ER function (hspa5, pdia6, ero1l, xbp1, edem1) is consistent with the critical role played by the ER for TG folding and M a n u s c r i p t 14 maturation (Arvan et al, 1997;Baryshev et al, 2004;Sargsyan et al, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In response to TSH stimulation, the thyroid tissue of all vertebrates produces and releases the same thyroid hormones (TH), thyroxine (T 4 ) and 3,5,3'-triiodothyronine (T 3 ), which play important roles for development, growth and metabolism (Leatherland, 1982;McNabb, 2007;Shi, 1999;Yen, 2001). Biosynthesis of TH is a multi-step process comprising iodide uptake by the sodiumiodide symporter (NIS), biosynthesis of thyroglobulin (TG), iodide organification by thyroid peroxidase (TPO) to yield iodothyronine-containing TG and finally, endocytosis and hydrolysis of iodinated TG to liberate TH (Dunn and Dunn, 2001). A hallmark of TSH action on thyroid follicular cells is to up-regulate the expression of many genes involved in TH synthesis and release (De Felice et al, 2004).…”
Section: Introductionmentioning
confidence: 99%